Elimination of mouse tumor cells from neonate spermatogonial cells utilizing cisplatin-entrapped folic acid-conjugated poly(lactic-co-glycolic acid) nanoparticles in vitro - Shabani R (Dove Medical Press, 2018)
Ronak Shabani,1,2 Mohsen Ashjari,3 Khadijeh Ashtari,1,4 Fariborz Izadyar,5 Babak Behnam,1,6,7 Samideh Khoei,8 Mohamad Asghari-Jafarabadi,9 Morteza Koruji1,2 1Cellular and Molecular Research Center, Iran University of Medical Sciences, Tehran, Iran; 2Department of Anatomical Sciences, School of Medicine, Iran University of Medical Sciences, Tehran, Iran; 3Department of Chemical Engineering, Faculty of Engineering, University of Kashan, Kashan, Iran; 4Department of Medical Nanotechnology and Faculty of Advanced Technology in Medicine, Iran University of Medical Sciences, Tehran, Iran; 5Prime Gen Biotech LLC, Santa Ana, CA, USA; 6Department of Medical Genetics and Molecular Biology, School of Medicine, Iran University of Medical Sciences, Tehran, Iran; 7NIH Undiagnosed Diseases Program, Common Fund, NHGRI, National Institutes of Health, Bethesda, MD, USA; 8Department of Medical Physics, School of Medicine, Iran University of Medical Sciences, Tehran, Iran; 9Road Traffic Injury Research Center, Tabriz University of Medical Sciences, Tabriz, Iran Background: Some male survivors of childhood cancer are suffering from azoospermia. In addition, spermatogonial stem cells (SSCs) are necessary for the improvement of spermatogenesis subsequent to exposure to cytotoxic agents such as cisplatin. Objective: The aim of this study was to evaluate the anticancer activity of cisplatin-loaded folic acid-conjugated poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) on mouse malignant cell line (EL4) and SSCs in vitro. Methods: SSCs were co-cultured with mouse malignant cell line (EL4) cells and divided into four culture groups: 1) control (cells were co-cultured in the culture medium), 2) co-cultured cells were treated with cisplatin (10 μg/mL), 3) co-cultured cells were treated with cisplatin-loaded folic acid-conjugated PLGA NPs, and 4) co-cultures were treated with folic acid-conjugated PLGA for 48 hours. The NPs were prepared, characterized, and targeted with folate. In vitro release characteristics, loading efficiency, and scanning electron microscopy and transmission electron microscopy images were studied. Cancer cells were assayed after treatment using flow cytometry and TUNEL assay. The co-cultures of SSCs and EL4 cells were injected into seminiferous tubules of the testes after treating with cis-diaminedichloroplatinum/PLGA NPs. Results: The mean diameter of PLGA NPs ranged between 150 and 250 nm. The number of TUNEL-positive cells increased, and the expression of Bax and caspase-3 were upregulated in EL4 cells in Group 4 compared with Group 2. There was no pathological tumor in testes after transplantation with treated co-cultured cells. Conclusion: The PLGA NPs appeared to act as a promising carrier for cisplatin administration, which was consistent with a higher activation of apoptosis than free drug. Keywords: spermatogonial cells, cancer cells, cisplatin, PLGA nanoparticles, drug delivery, folic acid